'Not Left in Limbo': Service User Experiences of Mental Health Nurse Prescribing in Home Care Settings. (3rd July 2021) - Frain, Sinead; Chambers, Liah; Higgins, Agnes; Donohue, Gráinne
Abstract: Prescribing in mental health nursing in the Republic of Ireland is still an unusual occurrence and despite an uptake in prescriber training, this does not often translate to practice. Recent Irish research, however, has identified that nurse prescribing when offered, is perceived to enhance care and offer better delivery of services. Since the legislation was introduced in the Republic of Ireland to enable nurses and midwives to prescribe in May 2007, there are now 1, 123 nurses registered to prescribe medication. Mental health nurses, however, do not tend to be a priority when it comes to training in prescribing; in the UK it took two years after nurse prescribing was rolled out to extend the scheme to mental health nursing. Although nurse and other professional perspectives explored this topic, there is limited research specifically detailing the experience of service users in long term care who are prescribed by mental health nurse practitioners in a home care setting. This research follows a qualitative exploratory research design using thematic analysis to explore service user (n = 12) experiences of mental health nurse prescribing. The following four themes emerged from the analysis: 'empowerment and trust'; 'person-centered care'; 'time and flexibility' and 'collaborative approach'. Results indicate a positive and rich experience of nurse prescribing, which facilitate a more trusting, holistic and autonomous therapeutic relationship. Future research looking at other issues relating to medication including reduction and support for coming off where appropriate is recommended